Efficacy and safety of HAT1 compared with calcipotriol in the treatment of patients with mild to moderate chronic plaque psoriasis: results from an open‐label randomized comparative pilot clinical study. (1st April 2020) - Alex, P.; Williams, S.; Sutton, L.; Yesudas, T.; Sutton, C.; Thomas, S.; Centola, M.
Summary: Psoriasis is commonly treated with topical corticosteroids, oral cytotoxic drugs and biologic agents, which can be associated with significant adverse effects (AEs), high cost and response attenuation. Additionally, patients often use alternative therapies ad hoc, which can be challenging to integrate into a treatment regimen, owing to a lack of adequately powered controlled trials assessing efficacy and safety. We developed a novel topical botanical complex, herbal anti‐inflammatory treatment (HAT1), through extensive preclinical in vitro and in vivo modelling to define key mechanisms of action and clinical potential. To assess the efficacy and safety of HAT1 in psoriasis, we performed a 10‐week, open‐label, pilot clinical trial comparing topical treatment of HAT1 with calcipotriol 0.005% in adult patients with mild to moderate psoriasis. Primary and secondary endpoints included the percentage of patients obtaining improvement of ≥ 75% in Psoriasis Area and Severity Index (PASI 75), Physician's Global Assessment (PGA) response, and evaluation of tolerability and safety of HAT1. In the HAT1 arm, 85.7% of study patients reached PASI 75 compared with 21.4% in the calcipotriol comparator group. Additionally, 78.6% of patients in the HAT1 arm achieved a 'clear' or 'minimal' PGA response. HAT1 was well tolerated, with no AEs observed throughout the trial. These results suggest that HAT1 reduces psoriasis disease activity in a clinically relevant manner. Ongoing studies, including well‐powered, double‐blind, randomized controlled trials will be required to assess the potential of HAT1 in psoriasis.